Effects of Sulphur-containing Compounds on Lettuce Fruit Germination - REYNOLDS, T. (Journal of Experimental Botany, 1974)
The germination of Lactuca sativa L. cv. Arctic King fruit on a 0.5 per cent agar substrate was inhibited in light at temperatures above 31C ( 1.0). This precisely repeatable value, termed the upper temperature cut-off point, is characteristic for this lettuce variety. The position of this cut-off point is raised by the presence of thiourea (500–1000 mg/1) and a number of other thiol compounds. This effect is not shown by all thiol compounds and is dependent on the configuration of the rest of the molecule. The presence of a hydroxyl group in the test compound often results in the temperature cut-off point being lowered but again this effect depends on the configuration of the rest of the molecule. It is postulated that the stimulating effects of active thiol compounds are related to hydrophobic interactions with a macro-molecule involved in the initiation of germination.